2008
DOI: 10.1177/239700220802200204
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Participation? Power Relations and Processes in Employee-owned Companies

Abstract: Introducing employee participation in a company can be expected to change the power relations and the power processes within the organization. This is particularly true when the majority ownership of a company moves into the hand of its employees. Drawing on three case studies of East German companies this paper describes how the introduction of employee ownership interrelates with power relations and processes in the company. Moreover, some overarching patterns were derived from the analysis finally resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Most often the share of capital on the employee side is very limited in relation to the total capital (Pendleton et al, 1998) and, consequently, the potential for control and participation in decision making does hardly exist (Blettner et al, 1995). Hammer and Stern (1980) found that the employees usually keep on regarding the management as the 'real' owners of the company and that they do not take any activity to change the internal power balance (similar Steger and Hartz, 2008). Van Dyne and Pearce (2004: 439) identified some positive effects of ESO on organisational commitment and pride, however their results "fail to show an incremental value of psychological ownership in predicting employee performance".…”
Section: Counter Arguments Inside the Discoursementioning
confidence: 97%
See 3 more Smart Citations
“…Most often the share of capital on the employee side is very limited in relation to the total capital (Pendleton et al, 1998) and, consequently, the potential for control and participation in decision making does hardly exist (Blettner et al, 1995). Hammer and Stern (1980) found that the employees usually keep on regarding the management as the 'real' owners of the company and that they do not take any activity to change the internal power balance (similar Steger and Hartz, 2008). Van Dyne and Pearce (2004: 439) identified some positive effects of ESO on organisational commitment and pride, however their results "fail to show an incremental value of psychological ownership in predicting employee performance".…”
Section: Counter Arguments Inside the Discoursementioning
confidence: 97%
“…Ends and assumed effects If the idea of 'economic participation' through ESO becomes connected with participation in the entrepreneurial process, this also raises several questions about power (distribution) in the company (Steger and Hartz, 2008). Pendleton and Poutsma (2004) point to the fact, that ESO could be interesting from the unions' perspective since it possesses some potential to increase industrial democracy.…”
Section: From Employee To Co-manager -Eso As a Means To Balance Powermentioning
confidence: 99%
See 2 more Smart Citations
“…All twenty acquiring companies interviewed had well-designed power point presentations defining the ESOP culture for their target company employees, because the new employeeownership culture certainly does not bloom overnight. Steger and Hartz (2008) report that during the cultural integration phase, the employee ownership culture needs to be woven into the daily business of the company and that how the employee owners view themselves is critical for the continued success of the employee ownership culture (pp.…”
Section: Interview 3 Pagementioning
confidence: 99%